Ehl-i Sünnet Fıkıh Mezheplerinin Hadis ve Rey Ekolü Olarak Sınıflandırılmasına Eleştirel Bir Bakış - Erdem, Mehmet (Dinî araştırmalar, 2006)
The majority of Moslems in our world are adherent of creed of Ahl al-Sunnah. In the classical Islamic literature, it is frequently said that the Sunni schools of fiqh were divided in two sects. One of them is Ahl al-Hadith (Traditionists) and the other one is Ahl ar-Ra’i (Rationalists,). Generally, it is accepted that the studies of fiqh in the Hicaz region were transformed into Hadith school and the studies of fiqh in the Iraq region were transformed into Ra’i school But there are a lot of contradictions among knowledges dealing with this issue as it isn’t known when this classification was done, and who were the representatives of these schools. Moreover there is no certain criterion for theese divisions. Besides, at the first sight, this division gives us an impression as if there is a deep rooted differences among Sunni schools’ approaching to traditions of Prophet. In this study, it is determined that the Sunni schools of fiqh have same attitude towards the Hadith and the Ray that form the axis of this division, and it is concluded that the division hasn’t established on the objective foundations